Stage IV Gastro‐Entero‐Pancreatic Neuroendocrine Neoplasms: A Risk Score to Predict Clinical Outcome. (23rd February 2017) - Panzuto, Francesco; Merola, Elettra; Pavel, Marianne Ellen; Rinke, Anja; Kump, Patrizia; Partelli, Stefano; Rinzivillo, Maria; Rodriguez‐Laval, Victor; Pape, Ulrich Frank; Lipp, Rainer; Gress, Thomas; Wiedenmann, Bertram; et al.
Abstract : Background: Several risk factors predict clinical outcome in gastro‐entero‐pancreatic neuroendocrine neoplasms (GEP‐NENs); however, the impact of their combination has not been investigated so far. Patients and Methods: A retrospective analysis of stage IV GEP‐NENs was performed. Multivariate analysis for progression of disease (PD) was performed by Cox proportional hazards method to obtain a risk score. Area under the curve obtained by receiver operating characteristic analysis was used to assess the score performance. Progression‐free survival analysis was performed by Kaplan‐Meier method. Results: Two hundred eighty‐three stage IV GEP‐NENs were evaluated, including 93 grade 1 neuroendocrine tumors (32.9%), 153 grade 2 neuroendocrine tumors (54%), and 37 grade 3 neuroendocrine carcinomas (13.1%). Independent risk factors for PD were Ki67, proportion of metastatic liver involvement, and presence of extra‐abdominal metastases. The risk score was calculated as follows: (0.025 × Ki67) + [(0 if no liver metastases or liver involvement <25%) OR (0.405 if liver involvement 25%–50%) OR (0.462 if liver involvement >50%)] + [(0 if no extra‐abdominal metastases) OR (0.528 if extra‐abdominal metastases present)]. The risk score accuracy to predict PD was superior compared with the G grading system (area under the curve: 0.705 and 0.622, respectively). Three subgroups of patients with low, intermediate, and high risk of PD according to risk score were identified, median progression‐free survival being 26 months, 19 months, and 12 months, respectively. Conclusion: In stage IV GEP‐NENs, a risk score able to predict PD was obtained by combining Ki67, proportion of metastatic liver involvement, and presence of extra‐abdominal metastases. The score may help to discriminate patients with different progression risk level to plan tailored therapeutic approaches and follow‐up programs. Abstract : The aim of this study was to identify, in a multi‐center international series of advanced gastro‐entero‐pancreatic neuroendocrine neoplasms, factors that can predict poor clinical outcome and to combine the variables to obtain a risk score. A risk score can quantify the risk of progression in these patients and may help physicians to plan the optimal therapeutic approach and follow‐up program